Complement C3b contributes to Escherichia coli-induced platelet aggregation in human whole blood - Landsem, Anne; Emblem, Åse; Lau, Corinna; Christiansen, Dorte; Gerogianni, Alexandra; Karlsen, Bård Ove; Mollnes, Tom Eirik; Nilsson, Per H.; Brekke, Ole-Lars (Frontiers in Immunology, 2022)
Introduction Platelets have essential functions as first responders in the immune response to pathogens. Activation and aggregation of platelets in bacterial infections can lead to life-threatening conditions such as arterial thromboembolism or sepsis-associated coagulopathy. Methods In this study, we investigated the role of complement in Escherichia coli (E. coli)-induced platelet aggregation in human whole blood, using Multiplate® aggregometry, flow cytometry, and confocal microscopy. Results and Discussion We found that compstatin, which inhibits the cleavage of complement component C3 to its components C3a and C3b, reduced the E. coli-induced platelet aggregation by 42%-76% (p = 0.0417). This C3-dependent aggregation was not C3a-mediated as neither inhibition of C3a using a blocking antibody or a C3a receptor antagonist, nor the addition of purified C3a had any effects. In contrast, a C3b-blocking antibody significantly reduced the E. coli-induced platelet aggregation by 67% (p = 0.0133). We could not detect opsonized C3b on platelets, indicating that the effect of C3 was not dependent on C3b-fragment deposition on platelets. Indeed, inhibition of glycoprotein IIb/IIIa (GPIIb/IIIa) and complement receptor 1 (CR1) showed that these receptors were involved in platelet aggregation. Furthermore, aggregation was more pronounced in hirudin whole blood than in hirudin platelet-rich plasma, indicating that E. coli-induced platelet aggregation involved other blood cells. In conclusion, the E. coli-induced platelet aggregation in human whole blood is partly C3b-dependent, and GPIIb/IIIa and CR1 are also involved in this process.